Does the etiology of infertility have any effect on perinatal outcomes? - Songül Alemdaroğlu; Gülşen Doğan Durdağ Şafak Yılmaz Baran; Tayfun Çok; Erhan Şimşek; Esra Bulgan Kılıçdağ Ebru Tarım (Perinatal Medicine Foundation, 2021)
Objective Pregnancies after in vitro fertilization (IVF) are associated with a less favorable outcome compared to natural conception as consistently shown in various studies. However, etiologic factors behind this issue remain to be elucidated. We aimed to demonstrate whether the etiology of infertility has a role on poor pregnancy outcomes in IVF pregnancies. Methods In this retrospective case control study; IVF and spontaneous singleton pregnancies were investigated. The infertile patients were divided into six groups according to the etiology of their infertility (anovulation, male factor, tubal factor, endometriosis, unexplained infertility and poor ovarian reserve). The incidence of preeclampsia, gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, preterm birth and birth weight discrepancies was examined between the groups and subgroups. After adjusting the confounding variables for each infertility subgroup such as demographic data, embryo stage in transfer (blastocyst against cleavage stage) and fresh and frozen embryo transfer status, the effect on pregnancy outcomes was investigated using multinomial logistic regression analysis. Results The study included 934 patients in the IVF group and 1009 patients in the control group. While adverse pregnancy outcomes were more frequent in the general infertility group in comparison to the control group, after elimination of the confounding variables, the direct effect of the etiology of infertility on these outcomes could not be shown. Conclusion In the IVF pregnancies, most of the increased risk of poor pregnancy outcomes appeared to be explained by maternal characteristics (such as age, body mass index) and by treatment protocols rather than infertility etiology. Physicians should consider these risks while counselling patients.